Mindfulness meditation and art appreciation as meaning-making practices - Yang, Charlie (Academy of Management Proceedings, 2016)
Mindfulness has recently gained significant attention and momentum in academia and popular culture. There is, however, a paucity of literature on how students make sense of contemplative practices. This paper proposes that mindfulness meditation is not merely a useful tool for stress reduction, but also a metacognitive meaning-making practice.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/021-315-407-614-417
Keywords: Art appreciations; Contemplative practice; Meaning makings; Metacognitives; Popular cultures; Stress reduction; dept.mgt

Making sense of mindfulness in management education - Yang, Charlie (Developing a Sustainability Mindset in Management Education, 2018)
Keywords: dept.mgt